Musik Tradisional Kolintang sebagai Terapi Pastoral Konseling di Tomohon - Oba, Monica Erika Gracia; Brek, Yohan; Ester Karosekali (PT. Giat Konseling Nusantara, 2025)
Culture as a complex and dynamic system covers all aspects of human life including knowledge, beliefs, art, and social norms. One of the rich forms of culture is traditional music such as Kolintang in Minahasa, which not only has aesthetic value but also functions as a therapeutic tool. Kolintang, a percussion instrument made of wood, has an important role in various traditional ceremonies and social life of the Minahasa people, especially in Tomohon City. This study examines the potential of traditional Kolintang music as a pastoral counseling therapy that can support the mental and spiritual health of individuals. Kolintang music therapy serves to express emotions, reduce stress, and strengthen social connectedness. It also plays a role in the process of emotional and spiritual healing, as well as assisting in self-development and the achievement of personal goals. Using a qualitative approach, this study explores how the integration of Kolintang music in culture-based pastoral counseling can provide emotional and psychological support, strengthen cultural identity, and improve individual well-being. As a cultural heritage, Kolintang not only preserves cultural values, but also becomes an effective tool in pastoral counseling therapy that strengthens spiritual and social relationships in society.